Liquid metal enabled elastic conductive fibers for self-powered wearable sensors - Zhang, Yue (2023)
Realizing stretchable conductive fibers with a trade-off between stretchability and conductivity is important for wearables. Fibrous triboelectric nanogenerators (FTENGs) represent a promising device for wearable power sources and self-powered sensors. However, the relationship between conductivity and triboelectric outputs of FTENG remains unfathomed. Herein, a simple strategy for fabricating stretchable conductive fibers with binary rigid-soft conductive components and dynamic compensation conductive capability is reported. Wet-spun thermoplastic polyurethane (TPU)/silver flakes (AgFKs) (TA) composite fiber is fabricated and coated by a water-borne polyurethane (WPU) thin layer, bridging the subsequent liquid metal (LM) coating to obtain TPU/AgFKs/WPU/LM (TAWL) fibers. The TAWL fiber shows outstanding elongation (~600% strain), electrical conductivity of ~2 Ω cm−1 (~3125 S cm−1), and reversible resistance response within 70% tensile strain. Encapsulated by polydimethylsiloxane (PDMS), the TAWL fiber is demonstrated as single electrode FTENG with the maximum output voltage, current, and transferred charge of 7.5 V, 167 nA, and 3.2 nC, respectively. The FTENG shows 150% stretchability without output dropping, demonstrating the superiority of TAWL fibers to sustain large deformation and conductivity degradation but maintain stable triboelectric outputs. As self-powered sensors, the FTENG can detect joint bending such as for fingers, elbows, and knees, as well as for pressure and location identification.